Reflections of a Zen Buddhist nun - Gim, Il yeob (Korean classics library, 2014)
Preface -- Life -- Buddhism and culture -- In memory of the Great Master Man'gong on the fifteenth anniversary of his death -- On New Year's day of the Twenty-Fifth year after joining the monastery -- A proposal to the World Fellowship of Buddhists Conference -- Why has Buddhism launched a purification movement? -- Is the mind one or two? To Mr. C., who has recently converted to Catholicism -- What is faith? Contemplation upon reading a letter from my friend M. -- The path to no-mind : a letter to Mr. R. -- Having burned away my youth : a letter to Mr. B. -- With a returned gift in my hand -- Having prepared a clean copy of my master's manuscript (by Yi Wolsong) -- Return to emptiness -- Meditation and the attainment of the mind -- Prayer and chanting -- Path to eternity : a message to journalists